Survey of ICT and Education in Africa : Equatorial Guinea Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of a larger Information for Development Program (infoDev)-supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. In Equatorial Guinea, there is no specific policy concerning ICT, although attempts to improve management in the Ministry of Telecommunications are being made. This could help facilitate the adoption of such a policy in the near future. The efforts to strengthen the presence of ICT in communities and in schools are primarily made by non-governmental organizations, universities, and other actors. They collaborate on projects that make computer equipment, training, and management available and accessible to students, educators, and members of the community. These initiatives take the form of computer labs in schools or media centre's in the community.